Correlation of Fc Receptor Polymorphisms with Pneumococcal Antibodies in Vaccinated Kidney Transplant Recipients - Arnold, Martin; Heinemann, Falko M.; Oesterreich, Simon; Wilde, Benjamin; Gackler, Anja; Goldblatt, David; Spriewald, Bernd; Horn, Peter A.; Witzke, Oliver; Lindemann, Monika (Vaccines, 2022)
Several polymorphisms within Fc receptors (FCR) have been described, some of which correlate with allograft function. In the current study, we determined three Fc gamma receptor and five Fc alpha receptor dimorphisms in 47 kidney transplant recipients who had been vaccinated against Streptococcus pneumoniae. We analyzed if FCR genotypes correlated with pneumococcal antibodies and their serotype-specific opsonophagocytic function, tested prior to and at months 1 and 12 post-vaccination. In parallel, we assessed antibodies against HLA and MICA and determined kidney function. We observed that IgG2 antibodies against pneumococci at months 1 and 12 after vaccination and IgA antibodies at month 1 differed significantly between the carriers of the three genotypes of FCGR3A rs396991 (V158F, p = 0.02; 0.04 and 0.009, respectively). Moreover, the genotype of FCGR3A correlated with serotype-specific opsonophagocytic function, reaching statistical significance (p < 0.05) at month 1 for 9/13 serotypes and at month 12 for 6/13 serotypes. Heterozygotes for FCGR3A had the lowest antibody response after pneumococcal vaccination. On the contrary, heterozygotes tended to have more antibodies against HLA class I and impaired kidney function. Taken together, our current data indicate that heterozygosity for FCGR3A may be unfavorable in kidney transplant recipients.
CRIS-Team WoS Importer:2022-06-10